Molecular cloning and biochemical characterization of a myotoxin inhibitor from Bothrops alternatus snake plasma - Santos-Filho, Norival A.; Fernandes, Carlos A. H. [UNESP]; Menaldo, Danilo L.; Magro, Angelo J. [UNESP]; Fortes-Dias, Consuelo L.; Estevao-Costa, Maria Inacia; Fontes, Marcos R. M. [UNESP]; Santos, Camila R.; Murakami, Mario T.; Soares, Andreimar M. (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
Phospholipases A(2) (PLA(2)s) are important components of Bothrops snake venoms, that can induce several effects on envenomations such as myotoxicity, inhibition or induction of platelet aggregation and edema. It is known that venomous and non-venomous snakes present PLA(2) inhibitory proteins (PLIs) in their blood plasma. An inhibitory protein that neutralizes the enzymatic and toxic activities of several PLA2s from Bothrops venoms was isolated from Bothrops alternatus snake plasma by affinity chromatography using the immobilized myotoxin BthTX-I on CNBr-activated Sepharose. Biochemical characterization of this inhibitory protein, denominated alpha BaltMIP, showed it to be a glycoprotein with Mr of similar to 24,000 for the monomeric subunit. CD spectra of the PLA(2)/inhibitor complexes are considerably different from those corresponding to the individual proteins and data deconvolution suggests that the complexes had a relative gain of helical structure elements in comparison to the individual protomers, which may indicate a more compact structure upon complexation. Theoretical and experimental structural studies performed in order to obtain insights into the structural features of aBaltMIP indicated that this molecule may potentially trimerize in solution, thus strengthening the hypothesis previously raised by other authors about snake PLIs oligomerization. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Phospholipase A(2); Myotoxin inhibitor; cDNA; Protein modeling; Molecular dynamics; Bothrops alternatus; Snake plasma